Lateral ventricular volume and calcarine sulcus depth: a fetal MRI analysis of mild ventriculomegaly. Issue 25 (19th June 2020) - Zhao, Si-xiu; Ma, Hong-li; Lv, Fu-rong; Zhang, Zhi-wei; Chen, Bo; Xiao, Yun-hua
Abstract : Abstract: The aim of this study was to quantify changes in the lateral ventricular volume, the depth of the calcarine sulcus (CS), and apparent diffusion coefficient (ADC) values of occipital lobe in fetuses with isolated mild ventriculomegaly (IMVM) using MRI. Seventy-one fetuses with IMVM at 25 to 38 weeks gestational age (GA) and 58 fetuses with normal lateral ventricles at 25 to 38 weeks GA were enrolled. Volumes of the lateral ventricles were measured by 3D magnetic resonance hydrography. Depths of the CS and ADC values were also evaluated. All differences were tested by t test. Bivariate correlations were performed using Pearson method. Fetuses with IMVM had significantly larger lateral ventricular volumes and smaller CS depths than controls (volumes: 9.37 ± 2.20 mL vs 5.04 ± 1.33 mL, respectively, P < .001; depths: 8.27 ± 2.55 mm vs 10.30 ± 3.14 mm, respectively, P < .001). In IMVM cases, the CS depths were smaller on the side with the larger ventricle (8.10 ± 2.54 mm vs 9.59 ± 2.81 mm, P < .001). No differences were observed in occipital lobe ADC values between the2 groups (IMVM = 1.80 ± 0.24 μm 2 /ms; controls = 1.78 ± 0.28 μm 2 /ms, P > .05). Fetuses with IMVM had larger lateral ventricular volumes, shallower CS depths, but normal occipital lobe ADC values.